Steric hindrance controls pyridine nucleotide specificity of a flavin‐dependent NADH:quinone oxidoreductase. (31st October 2018) - Ball, Jacob; Reis, Renata A. G.; Agniswamy, Johnson; Weber, Irene T.; Gadda, Giovanni
Abstract: The crystal structure of the NADH:quinone oxidoreductase PA1024 has been solved in complex with NAD + to 2.2 Å resolution. The nicotinamide C4 is 3.6 Å from the FMN N5 atom, with a suitable orientation for facile hydride transfer. NAD + binds in a folded conformation at the interface of the TIM‐barrel domain and the extended domain of the enzyme. Comparison of the enzyme‐NAD + structure with that of the ligand‐free enzyme revealed a different conformation of a short loop (75–86) that is part of the NAD + ‐binding pocket. P78, P82, and P84 provide internal rigidity to the loop, whereas Q80 serves as an active site latch that secures the NAD + within the binding pocket. An interrupted helix consisting of two α‐helices connected by a small three‐residue loop binds the pyrophosphate moiety of NAD + . The adenine moiety of NAD + appears to π–π stack with Y261. Steric constraints between the adenosine ribose of NAD +, P78, and Q80, control the strict specificity of the enzyme for NADH. Charged residues do not play a role in the specificity of PA1024 for the NADH substrate. Abstract : PDB Code(s):6E2A